2014
DOI: 10.1002/hbm.22571
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neural responses to conscious versus unconscious monetary reward cues

Abstract: Human reward pursuit is often assumed to involve conscious processing of reward information. However, recent research revealed that reward cues enhance cognitive performance even when perceived without awareness. Building on this discovery, the present functional MRI study tested two hypotheses using a rewarded mental-rotation task. First, we examined whether subliminal rewards engage the ventral striatum (VS), an area implicated in reward anticipation. Second, we examined differences in neural responses to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…65,71,72 Indeed, SMA activity has been consistently found during reward anticipation. [73][74][75][76] Our finding therefore suggests decreased reward-based motor preparation in siblings.…”
Section: Discussionmentioning
confidence: 57%
“…65,71,72 Indeed, SMA activity has been consistently found during reward anticipation. [73][74][75][76] Our finding therefore suggests decreased reward-based motor preparation in siblings.…”
Section: Discussionmentioning
confidence: 57%
“…However, when rewards were presented after the word, that is, during the active maintenance processing, performance increased when high rewards were presented subliminally, but decreased when they were presented supraliminally. Finally, Bijleveld et al (2014) studied the neural bases of subliminal and supraliminal monetary reward during a mental-rotation task fMRI study. They found that delivery of conscious and unconscious rewards produced the same behavioral outcomes.…”
Section: Does Motivational Attention Require Consciousness?mentioning
confidence: 99%
“…Indeed, the striatum has a central role in learning as it is sensitive to prediction errors (Dreher, 2013;Vink et al, 2013), although this is almost exclusively studied in the context of reward processing and not response inhibition. Indeed, the expectation of reward is associated with striatal activation (O' Doherty, 2004;Bijleveld et al, 2014;Pas et al, 2014).…”
Section: Stimulus and Response Periodmentioning
confidence: 99%